The Human Vaccines Project: Towards a comprehensive understanding of the human immune response to immunization - Stacey L. Wooden; Wayne C. Koff (Taylor & Francis Group, 2018)
Although the success of vaccination to date has been unprecedented, our inadequate understanding of the details of the human immune response to immunization has resulted in several recent vaccine failures and significant delays in the development of high-need vaccines for global infectious diseases and cancer. Because of the need to better understand the immense complexity of the human immune system, the Human Vaccines Project was launched in 2015 with the mission to decode the human immune response to accelerate development of vaccines and immunotherapies for major diseases. The Project currently has three programs: 1) The Human Immunome Program, with the goal of deciphering the complete repertoire of B and T cell receptors across the human population, termed the Human Immunome, 2) The Rules of Immunogenicity Program, with the goal of understanding the key principles of how a vaccine elicits a protective and durable response using a system immunology approach, and 3) The Universal Influenza Vaccine Initiative (UIVI), with the goal of conducting experimental clinical trials to understand the influence of influenza pre-exposures on subsequent influenza immunization and the mechanisms of protection. Given the dramatic advances in computational and systems biology, genomics, immune monitoring, bioinformatics and machine learning, there is now an unprecedented opportunity to unravel the intricacies of the human immune response to immunization, ushering in a new era in vaccine development.